Conbiomics: the missing approach for the conservation of freshwater bivalves - Froufe, Elsa (2018)
The decline of freshwater biodiversity hás reached alarming proportions. The extinction rate of freshwater biodiversity is predicted to be five times faster than ali other groups of species. The Unionidae, being the largest of the freshwater bivalve families, is among the most endangered group in the world. They are important providers of aquatic ecosystem services and are characterized by an unusual pattem of mtDNA inheritance. However, phylogeny, population genetic structure and species-level diversity remains unclear for much of the group. With an experienced and well-qualified team, the present proposal aims to define the most important freshwater mussel taxa and most criticai áreas for conservation, at European and Global leveis, to inform the most relevant policy niakers. This will be achieved by integrating a genomics approach with available distribution data, in order to determine and map global species richness, phylogenetic diversity, and weighted endemism. This complementary approach will not only help conserve this vulnerable group but will offer wider benefits to freshwater ecosystems whose billions of people depend globally. Additionally, as these animals have an extraordinary unusual pattern of mtDNA inheritance, they will be used as model-taxa to study the evolution of mtDNA and life in general.